﻿Two new genera (Vittiblatta gen. nov. and Planiblatta gen. nov.) of Blattinae (Blattodea, Blattidae) from Southwest China and the discovery of chirally dimorphic male genitalia in Vittiblatta punctata sp. nov. - Xin-Xing Luo; Wen-Bo Deng; Yan-Li Che; Zong-Qing Wang (ZooKeys, 2023)
This study examines Blattinae samples from Southwest China collected in recent years. Based on morphological characters, we establish two genera, Vittiblatta gen. nov. and Planiblatta gen. nov., and describe four new species, Vittiblatta punctata Luo & Wang, sp. nov., Vittiblatta ferruginea Luo & Wang, sp. nov., Vittiblatta undulata Luo & Wang, sp. nov., and Planiblatta crassispina Luo & Wang, sp. nov. These two new genera resemble Periplaneta s.s., but are easily distinguished from it and other genera of Blattinae by morphological characters (genital sclerite L4C). Our results indicate that sclerites L4C and R1G of male genitalia might be important in species delimitation of Blattinae. In addition, chiral dimorphism is found in male genitalia of Vittiblatta punctata sp. nov.